2020
DOI: 10.1177/1461444820963795
|View full text |Cite
|
Sign up to set email alerts
|

A question of perspective: Exploring audiences’ views of journalistic boundaries

Abstract: While scholarship has studied the boundary discourses of (quasi-)journalistic actors on social network sites, how audiences perceive these boundaries and engage with these interlopers’ work has been examined far less frequently. Drawing on 11 focus groups, this article explores how audiences construct boundaries by examining and comparing their expectations of content creators on Instagram, YouTube and blogs, with traditional journalism and journalists. Findings show audiences expect journalists to embody esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 56 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…This study aims to fill this gap in research on alternative media by connecting audience evaluations to outlets' self-characterization as "alternative". We orient ourselves to recent theoretical discussions highlighting the importance of an audience perspective in identifying the boundaries of journalism (Banjac and Hanusch 2020;Tandoc and Duffy 2016). These studies all showed that audiences are increasingly becoming conscious of what journalism is (Tandoc and Duffy 2016) while simultaneously recognizing that different players can fulfil expectations from both traditional and non-traditional journalism (Banjac and Hanusch 2020) as so-called interlopers (Eldridge 2019).…”
Section: Difficulties In Defining Alternative News Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…This study aims to fill this gap in research on alternative media by connecting audience evaluations to outlets' self-characterization as "alternative". We orient ourselves to recent theoretical discussions highlighting the importance of an audience perspective in identifying the boundaries of journalism (Banjac and Hanusch 2020;Tandoc and Duffy 2016). These studies all showed that audiences are increasingly becoming conscious of what journalism is (Tandoc and Duffy 2016) while simultaneously recognizing that different players can fulfil expectations from both traditional and non-traditional journalism (Banjac and Hanusch 2020) as so-called interlopers (Eldridge 2019).…”
Section: Difficulties In Defining Alternative News Mediamentioning
confidence: 99%
“…We orient ourselves to recent theoretical discussions highlighting the importance of an audience perspective in identifying the boundaries of journalism (Banjac and Hanusch 2020;Tandoc and Duffy 2016). These studies all showed that audiences are increasingly becoming conscious of what journalism is (Tandoc and Duffy 2016) while simultaneously recognizing that different players can fulfil expectations from both traditional and non-traditional journalism (Banjac and Hanusch 2020) as so-called interlopers (Eldridge 2019). Furthermore, audiences are a valuable resource for researchers studying news media performance crossnationally, as audience evaluations come to similar conclusions as traditional content analyses (Steppat, Castro Herrero, and Esser 2020).…”
Section: Difficulties In Defining Alternative News Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…This is further corroborated by recent studies finding that newspapers are perceived as less hostile and closer to one’s own political convictions than TV ( Bachl, 2016 ). Nevertheless, newspaper journalism still aims to differentiate itself from other non-professional content generators by employing specific journalistic roles and standards, for example, objectivity and disseminator ( Banjac and Hanusch, 2020 ).…”
Section: Media Fragmentation and Polarization As Opportunity Structuresmentioning
confidence: 99%
“…Although, they comprise journalism's role in society and its contribution to a functioning democracy. Journalistic norms have been an anchor point to investigate the publics' expectations (example: Tsfati et al 2006) and recent findings already indicated that media users expect journalists to fulfil these journalistic roles (Banjac and Hanusch 2020). Therefore, we assume them to be convenient and suitable concepts to compare views on journalism of different types of news users.…”
Section: Journalistic Professional Normsmentioning
confidence: 99%